Numerical investigation of impact of misfires and out-of-sequence delays on fragmentation and gravity flow in SLC - C. Yi; D. Johansson; C. San Miguel; M. Wimmer (International Society of Explosives Engineers, 2024)
Sublevel caving (SLC) is a mass mining method based upon the utilization of gravity flow of blasted ore and caved waste rock. Production blasting has significant impact on the efficiency and productivity of SLC output, affecting material fragmentation, flow and recovery. Misfires could occur during blasting in SLC, which results in the loss of explosives and poor fragmentation. Usually, the blastholes are top-initiated with redundant lower primers set at + 25 ms as a precaution. If the top primers fail, the lower primers may initiate the explosive, which will induce out-of-sequence delays that can influence fragmentation and gravity flow. This work investigated the impact of misfires and out-ofsequence delays on fragmentation and gravity flow through numerical simulations using a coupled finite element and discrete element method. Different scenarios of misfires and out-of-sequence delays were studied, and the fragment size distribution was obtained to evaluate the blasting performance. The material flow behaviour was investigated to assess the gravity flow process. The results indicated that misfires significantly affect the fragmentation and the gravity flow process while the effects of out-of-sequence delays are not so significant for the investigated cases